Acquiring the Impossible: Developmental Stages of Copredication - Murphy, Elliot (Frontiers in Psychology, 2017)
Much is known about the acquisition of phonological competence and lexical categories, but there has been substantially less research into word meaning development. In an attempt to contribute to this debate, a group of 24 children aged 4-11 were asked to define a set of words, as were a group of 12 adult controls. The stimuli included both concrete and abstract words, in particular words exhibiting a rare form of polysemy known as copredication, which permits the simultaneous attribution of concrete and abstract senses to a single nominal, creating an ‘impossible’ entity. The results were used to track the developmental trajectory of copredication, previously unexplored in the language acquisition literature.